Anti-retinal IgG antibodies in patients with early and advanced type 2 macular telangiectasia. (May 2022) - McLenachan, Samuel; Balaratnasingam, Chandrakumar; Heath Jeffery, Rachael C.; Chen, Shang-Chih; Zhang, Dan; Chan, Geoffrey; Dolz-Marco, Rosa; Bacci, Tommaso; Lo, Johnny; Wiffen, Steven; Yannuzzi, Lawrence A.; Chen, Fred K.
Abstract: Type 2 idiopathic macular telangiectasia (MacTel-2) is a progressive adult-onset macular disease associated with bilateral perifoveal vascular changes, Muller cell degeneration and increased blood-retinal barrier permeability. The pathophysiological mechanisms of MacTel-2 remain unclear, however it was previously reported that anti-retinal antibodies in MacTel-2 patients are a significant feature of the disease. In this study, we aimed to compare the prevalence of anti-retinal antibodies in patients MacTel-2, healthy controls and patients with other retinal diseases. MacTel-2 patients diagnosed with multimodal imaging were enrolled and their disease severities were graded using spectral-domain optical coherence tomography. For comparison, patients with age-related macular degeneration (AMD), inherited retinal diseases (IRDs) or no retinal disease (healthy controls) were recruited as controls. Blood serum samples were screened for immunoglobulin G anti-retinal antibodies by western blotting, followed by densitometry analysis. Odds ratios (OR) with 95% confidence intervals (CI) were calculated and p < 0.05 considered statistically significant. Overall, anti-retinal antibody-positive cases were older (64 ± 15 vs 53 ± 17 years, p < 0.001) and females were more likely to develop anti-retinal antibodies (OR: 2.41, CI: 1.12–5.18). The frequency of anti-retinal antibody detection in MacTel-2 patients (n = 42, 36%) was not significantly different from healthy controls (n = 52, 25%) or IRD patients (n = 18, 25%) and the majority of MacTel-2 patients had no anti-retinal antibodies. In contrast, the frequency of anti-retinal antibody detection was significantly higher in patients with AMD (n = 15, 73%, p < 0.001). The lack of a greater anti-retinal antibody frequency or specificity in the MacTel-2 cohort suggests that antibody mediated immunological mechanisms may play a less significant role in MacTel-2 disease pathogenesis. Highlights: Anti-retinal antibodies have previously been associated with MacTel-2. Anti-retinal antibody frequencies were compared between healthy controls and patients with MacTel-2. The majority of MacTel-2 patients were negative for anti-retinal antibodies. Anti-retinal antibodies are unlikely to play a role in MacTel-2.